Characterization of particulate organic matter in the Lena River delta and adjacent nearshore zone, NE Siberia – Part 2: Lignin-derived phenol compositions - M. Winterfeld; M. A. Goñi; J. Just; J. Hefter; G. Mollenhauer (Biogeosciences, 2015)
The Lena River in central Siberia is one of the major pathways translocating terrestrial organic matter (OM) from its vast catchment area to the coastal zone of the Laptev Sea and the Arctic Ocean. The permafrost soils of its far south-stretching catchment, which store huge amounts of OM, will most likely respond differently to climate warming and remobilize previously frozen OM with distinct properties specific for the source vegetation and soil. To characterize the material discharged by the Lena River, we analyzed the lignin phenol composition in total suspended matter (TSM) from surface water collected in spring and summer, surface sediments from Buor Khaya Bay along with soils from the Lena Delta's first (Holocene) and third terraces (Pleistocene ice complex), and plant samples. Our results show that lignin-derived cinnamyl : vanillyl (C / V) and syringyl : vanillyl (S / V) ratios are > 0.14 and 0.25, respectively, in TSM and surface sediments, whereas in delta soils they are > 0.16 and > 0.51, respectively. These lignin compositions are consistent with significant inputs of organic matter from non-woody angiosperm sources mixed with organic matter derived from woody gymnosperm sources. We applied a simple linear mixing model based on the C / V and S / V ratios, and the results indicate the organic matter in delta TSM samples and Buor Khaya Bay surface sediments contain comparable contributions from gymnosperm material, which is primarily derived from the taiga forests south of the delta, and angiosperm material typical for tundra vegetation. Considering the small catchment area covered by tundra (~ 12%), the input is substantial and tundra-derived OM input is likely to increase in a warming Arctic. The similar and high acid to aldehyde ratios of vanillyl and syringyl (Ad / AlV, S) in Lena Delta summer TSM (> 0.7 and > 0.5, respectively) and Buor Khaya Bay surface sediments (> 1.0 and > 0.9, respectively) suggest that the OM is highly degraded and Lena River summer TSM could be a possible source of the surface sediments. The Ad / AlV, S ratios of the first and third delta terraces were generally lower (mean ratios > 0.4 and > 0.4, respectively) than summer TSM and surface sediments. This implies that TSM contains additional contributions from a more degraded OM source (southern catchment and/or finer more degraded particle size). Alternatively, OM degradation on land after permafrost thawing and subaqueously during transport and sedimentation could be considerable. Despite the high natural heterogeneity of OM stored in delta soils and exported by the Lena River, the catchment-characteristic vegetation is reflected by the lignin biomarker composition. Climate-warming-related changes in the Lena River catchment may be detectable in changing lignin biomarker composition and diagenetic alteration.